Food security in rural areas: the case of the Umkhanyakude District Municipality in the Northern Region of KwaZulu-Natal - Nhlozi, Mduduzi W (My University, 2024)
Studies on food security focusing on households began attracting considerable attention in the mid-1970s following a surge in the cost of food production and food prices. The surge in prices led to increasing percentage of food insecure households throughout the world. To address the growing number of people affected by hunger, countries sought to develop new technological techniques to produce food in large quantities particularly in the developing world. The thrust of the approach was to ensure the availability of food first. The understanding was that large food quantities would result in food-secure nations. Overtime, researchers realised that improved food production does not lead to food secure households. Since then, the percentage of people affected by hunger has continued to increase with 690 million (8.9%) considered food insecure in 2020 (Food Agriculture Organisation – FAO, 2021) despite relative increase in food production. South Africa is not an exception with 23% of the population reported food insecure in 2020 (van der Berg et al., 2021). The reports by the NIDS-CRAM have indicated that the outbreak of coronavirus pandemic in 2019 has further exacerbated food insecurity at a household level. The purpose of the study is to explore mechanisms used by rural households to achieve food security during various threats and risks to their livelihoods. The case study adopted is the Umkhanyakude region which is in the rural area of northern part of KwaZulu Natal. It covers an area of 13855.35 km² and accommodates approximately 625 846 people constituting a total of 128 195 households (Stats SA, 2011). The region was selected as a case study due to its economic, social, demographic and ecological characteristics. The study uses semistructured questionnaire to collect information on lived experiences of households in their quest to access and ensure availability of food. The study finds that households use several food strategies namely economy-related, culture-related and rite-of-passage to achieve food security. The strategies are framed within the context of what Nee and Ingram (1998) refer to as new institutionalism or new institutional economics. New institutional economics places focus on the importance of a “web of interrelated norms – formal and informal” that govern how individuals and households in Umkhanyakude region “respond to perception of costs and benefit in exchanges and invest in or divest themselves of particular ties” (Nee and Ingram, 1998: 19). The study argues that these strategies are embedded within social norms, values, and cultural practices beyond the ambit of orthodox economics. It further argues that the discourse on food security in rural areas must be framed beyond the economic analytical framework, to reckon with the embedded social and cultural norms, practices, rules, and relationships and to develop salient policy interventions. The study advocates for the development of localised food security plans by local municipalities to improve food security status of rural households. This is because food insecurity is largely felt at community and household levels. It is important that policy frameworks to manage food security are placed at municipal levels where local communities can easily access them.
A thesis submitted in fulfilment of the requirement for the degree Doctor of Philosophy (Town and Regional Planning) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2023
Keywords: Food security; Socio-cultural systems; Umkhanyakude